2022
DOI: 10.1093/ntr/ntac179
|View full text |Cite
|
Sign up to set email alerts
|

National and Regional Fraction of Cancer Incidence and Death Attributable to Current Tobacco and Water-Pipe Smoking in the Eastern Mediterranean Countries in 2020

Abstract: INTRODUCTION We aimed to calculate the Population Attributable Fraction (PAF) of cancers due to tobacco use in the Eastern Mediterranean Region (EMRO), where water-pipe smoking is prevalent but its effect was not considered in previous studies. METHODS We applied Levin's formula to estimate PAFs of cancers due to tobacco use (defined as all type tobacco including both cigarette and water-pipe). We also calculated PAF of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Using population-level data, we previously found that smoking tobacco contributes to 14% of incident cancers in the eastern Mediterranean region (26% in males, 3% in females). 29 In the current analysis, 8% of incident cancers were attributable to smoking cigarettes (12% in males, 2% in females). While the lower prevalence of smoking tobacco (particularly among females) in this region may explain the lower tobacco related PAFs in our study, using individual-level data that allowed obtaining PAFs that are adjusted for other confounders and risk factors may have also contributed to having lower estimates than other studies that used population-level data.…”
Section: Discussionmentioning
confidence: 55%
“…Using population-level data, we previously found that smoking tobacco contributes to 14% of incident cancers in the eastern Mediterranean region (26% in males, 3% in females). 29 In the current analysis, 8% of incident cancers were attributable to smoking cigarettes (12% in males, 2% in females). While the lower prevalence of smoking tobacco (particularly among females) in this region may explain the lower tobacco related PAFs in our study, using individual-level data that allowed obtaining PAFs that are adjusted for other confounders and risk factors may have also contributed to having lower estimates than other studies that used population-level data.…”
Section: Discussionmentioning
confidence: 55%
“…It is possible the CV effects resolve in most of the patients with cessation of WPS. Considering the other long-term complications, such as an increase in the incidence of cancer and death attributable to WPS, highlights the pressing need to encourage smoking cessation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses at the sub‐national level to verify PAFs of opium use and waterpipe smoking in the high prevalence regions may highlight the importance of these risk factors in cancer prevention in Iran. A recent study investigated the attributable fraction of waterpipe use at the national and regional levels in the EMR 56 . As waterpipe and opium use prevalence is growing worldwide, such studies are recommended globally for both waterpipe and opium use.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated the attributable fraction of waterpipe use at the national and regional levels in the EMR. 56 As waterpipe and opium use prevalence is growing worldwide, such studies are recommended globally for both waterpipe and opium use.…”
Section: Discussionmentioning
confidence: 99%